2009
DOI: 10.1186/1471-2458-9-491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phone versus mail survey methods on the measurement of health-related quality of life and emotional and behavioural problems in adolescents

Abstract: BackgroundTelephone interviews have become established as an alternative to traditional mail surveys for collecting epidemiological data in public health research. However, the use of telephone and mail surveys raises the question of to what extent the results of different data collection methods deviate from one another. We therefore set out to study possible differences in using telephone and mail survey methods to measure health-related quality of life and emotional and behavioural problems in children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 30 publications
3
32
1
4
Order By: Relevance
“…In einer methodischen Studie konnte gezeigt werden, dass der SDQ sensitiv gegenüber dem Erhebungsmodus ist [36]. Dabei wurden bei der Befragung mit der auch diesem Beitrag zugrunde gelegten Elternversion des SDQ mit Blick auf die Subskalen in der telefonischen Erhebung mehr Verhaltensprobleme und mehr prosoziales Verhalten, jedoch weniger Peer-Probleme berichtet als in der schriftlichen Befragung, bei allerdings geringen Effektstärken [36] …”
Section: Normwerte Und Cut-off-kriterienunclassified
See 2 more Smart Citations
“…In einer methodischen Studie konnte gezeigt werden, dass der SDQ sensitiv gegenüber dem Erhebungsmodus ist [36]. Dabei wurden bei der Befragung mit der auch diesem Beitrag zugrunde gelegten Elternversion des SDQ mit Blick auf die Subskalen in der telefonischen Erhebung mehr Verhaltensprobleme und mehr prosoziales Verhalten, jedoch weniger Peer-Probleme berichtet als in der schriftlichen Befragung, bei allerdings geringen Effektstärken [36] …”
Section: Normwerte Und Cut-off-kriterienunclassified
“…Mit Blick auf die Subskalen waren analog früherer Befunde die internen Konsistenzen für die Subskala "Hyperaktivität" am höchsten, diejenigen für die Subskala "Verhaltensprobleme" am geringsten [13,28,31]. Bei der telefonischen Erhebung in der KiGGS Welle 1 waren die internen Konsistenzen insgesamt etwas niedriger als beim schriftlichen Assessment in der KiGGS-Basiserhebung, was einem ähnlichen Befund der methodischen Vergleichsstudie von Erhart et al entspricht [36]. [47].…”
Section: Psychometrische Eigenschaftenunclassified
See 1 more Smart Citation
“…This finding has been observed in disease-specific groups, including SCI, as well as generic groups. [29][30][31][32] Given the likelihood that systematic differences in HRQoL could be attributable to the method of data collection alone, an explicit objective of the current review is to establish the state-ofplay for alternative modes of survey administration in the context of SCI. Due to fundamental differences in measurement objectives between profile measures of HRQoL (such as the SF-36 and SF-12) and utility instruments (e.g.…”
Section: Objective and Evaluative Frameworkmentioning
confidence: 99%
“…Postal interviews were found to have higher completion rates than telephone interviews (Erhart et al, 2009;McHorney et al, 1994) and face-to-face interviews (Smeeth et al, 2001). However, postal interviews were also characterised by higher percentages of missing data (McHorney et al, 1994;Smeeth et al, 2001), although Hawthorne et al (2003) reported no significant differences between the rate of missing data for telephone and postal interviews.…”
mentioning
confidence: 99%